Optimality and correspondence theories in phonological shifts: a case study on Arabic guttural consonants in English loanwords - Alhaider, Siham (Frontiers in Language Sciences, 2025)
The standardization of loanwords presents challenges for borrowers due to phonological adaptations, particularly with guttural speech sounds. This case study examined native English speakers' articulation of Arabic loanwords containing guttural consonants, applying optimality theory and correspondence theory to investigate phonetic and phonological constraints. The analysis revealed that participants experienced difficulty adhering to constraints in their articulation, resulting in the omission, repair, or replacement of guttural phones in Arabic loanwords. Contrary to initial assumptions, the study found that deletion and replacement mechanisms were not exclusively position-dependent but rather determined by specific guttural sounds. For example, replacement occurred with sounds such as /χ/, /q/, and /g'/, while deletion was applied to sounds like /ʕ/, /ʔ/, and /ħ/. The repair strategy, however, was observed to be position-dependent, occurring only with words containing a medial guttural. These findings contribute to the understanding of phonological adaptations in loanwords and the interrelationships among significant linguistic groups, highlighting the complex nature of guttural consonant articulation in cross-linguistic contexts.